ELECTRON IMPACT STUDIES ON SOME ETHYL 2,3-DIOXOBUTYRATE-2-PHENYLHYDRAZONES: Short Communication (Biological Sciences - PJSIR, 2001)
The present communication deals with the electron impactstudies on ethyl 2,3-dioxobutyrate-2-phenylhydrazones andrelated substituted phenylhydrazones containing electron releasingas well as electron withdrawing substituents on thephenyl nucleus. The formation of base peaks were greatlyinfluenced by the nature of substituent in the phenyl nucleus.Neutral and radical loss from the aromatic subtituents werealso found to depend upon the nature of groups. Thesehydra zones undergo thermal isomerisation to azo form whichfragments subsequently to daughter ions in accordance withthe azo structure having very low relative intensity and L